Finding Conceptual Framework and Critial KPI’s For Performance Management System For Field Instrumentation Team of Private Ownership Construction Consultant: A Case Study - Ahmad Kemal Arsyad; Dermawan Wibisono (Syntax Literate, 2022)
Monitoring works is considered have significant impact on the office's internal processes, the propper PMS is needed. This study aims to manage the organizational performance of PT XYZ company using Knowledge Based Performance Management System (KBPMS) framework approach developed by Wibisono (2006). The proposed model was developed by combining a literature review and a case study approach applied to construction companies especially from previous studies in Indonesia. The data is analyzed to assess the suitability of the company's strategy with the current PMS used in the company, and to determine suitable performance indicators to be used in the proposed model. The analysis was carried out using a qualitative approach and multi-criteria decision-making with an analytical hierarchy process (AHP) approach from experts at the managerial level of the company. The research shows that there are at least 16 aspects and 20 performance measurement variables proposed for the monitoring division to support PT XYZ's performance. The development of this model is still in a stage that needs to be developed further. Evaluation and improvement of the PMS implementation will be planned in the future.